Analisis Uji Kelayakan Penerapan Media Pembelajaran Instalasi Motor Listrik Berbasis Augmented Reality - Hazmi Sidiq; Mukhlidi Muskhir (Jurnal Pendidikan Teknik Elektro, 2020)
Electric motor installation learning in Vocational High School (SMK) is often problematic because students have not been able to adapt to the self-directed learning system implemented by teachers. In addition, the media used in the self-learning process is still less effective, because it only uses learning modules. Therefore, students have difficulty in understanding the subject matter of the installation of electric motors. The purpose of this research is to create Learning media based on Augmented Reality that is feasible for electric motor installation subjects. Developed learning media are equipped with manuals and markers. This research uses Research and Development (R & D) method using a 4-D model through four stages namely stage I (define), stage II (design), stage III (develop), and stage IV (disseminate). Learning media based on AR was tested on 28 students of SMK Negeri 1 Padang at grade XI TITL A and 29 students at grade XI TITL B. The results of the average feasibility test of grade XI TITL A and grade XI TITL B were 86.63% in the highest feasible category.